Nosaviraka’s Ritual Mantra on The Quran And Hadits: Intertextual Analysis - Ida Nuraeni; Yunidar Yunidar; Akbar Akbar (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2023)
This intertextual analysis of the mantras in the Nosaviraka healing ritual does not intend to compare the contents of the Quran and Hadits with the oral text of the mantras because the Quran is a sacred divine word without the intervention of creatures. The study aims to describe the relationship between Nosaviraka healing ritual, the Kaili tribe in Central Sulawesi and the the Quran and Hadits. The method used in this research is descriptive qualitative with an intertextual approach. The data source for this research is Nosaviraka healing ritual. The data in the form of the arrays in the mantras were analyzed using the intertextual theory, namely determining the link between the arrays of the mantras and the Quran and Hadits. Based on the research results obtained three findings. First, here is a relationship between the text of the Nosaviraka mantra and the text of the Quran and Hadits. This relationship is shown in all parts of the mantra, namely (a) the initial mantra of agreement, (b) the mantra of summoning ancestors, (c) the mantra of healing, (d) the mantra of salvation, and (e) the mantra of the end. Second, the Nosaviraka ritual mantra as a hypogram, while the text of the Quran and Hadits as the owner of the transformation. Directly or indirectly, the Nosaviraka mantra, the Quran, and the Hadits can be seen from the similarity in structure, but the use of imagination is slightly different in theme. Third, there is a strong tendency that the Nosaviraka mantra is a form of belief in Allah SWT which is associated with the Quran as its hypogram.